Integrated Process of Biosurfactant Production by Bacillus atrophaeus ATCC-9372 Using an Air-Lift Bioreactor Coupled to a Foam Fraction Column - Rocha, Maria de Fátima F. (2023)
Biosurfactants are surface-active molecules, produced by several microorganisms, that possess unique properties such as low toxicity and biodegradability. Their application in various industries depends on their purity and their specific properties, such as emulsification and stability. Therefore, this study focuses on the production of biosurfactant from Bacillus atrophaeus in an air-liftbioreactor. It analyzes the effects of agitation rate and temperature on biosurfactant production, as well as the concurrent separation process using a foam fractionation column. Moreover, the ability of the produced biosurfactant to form emulsions in water with several substrates (vegetables oils, hydrocarbons, and fossil fuels) was determined, and the stability of the soybean oil?water emulsion (used as an example) at different temperatures and pH values was verified. The biosurfactant produced, tentatively identified as iturin, was only detected in the coalescent liquid after passing through the foam fractionation column, demonstrating the complete separation of the biosurfactant. The best operational conditions for production and separation were an air flow of 1.00 vvm and a temperature of 34 ◦C (emulsifier index (EI24) = 66.9%, and productivity (Pp) = 967.5% mL h−1 ). Vegetable oils, hydrocarbons, and fossil fuels were emulsified in water, highlighting the soybean oil,whose emulsion oil?water had the highest ES (3333.3 min) at a temperature of 50 ◦C and a pH value of 9.0.